GAME LEARNING FISIKA “ASAH OTAK” BERBASIS ANDROID DENGAN APP INVENTOR 2 - Rizky Parlika; Luthfiyatul ‘Azizah; Anggoro Cahyo Nugroho; Devi Anugrah Putri; Stevanus Frangky Handono (Universitas Narotama, 2018)
Abstract : Serious game is one of the kind that made not only for entertaiment but also has other functions such as learning or education, training, advertising, simulation, health and others. Nowadays many games are already used as a learning or education. Educational games are usually applied based on age stages or its genre. Educational games can help to train The thinking ability and the logic skill for it players. The learning methods that using games are expected to be more interesting and understandable for it players. This paper is discussed about an educational game concept as a learning media for high school students specialized for physics subject. This game is an android-based game that expected to be directly implemented into their smartphones and can be played anywhere. This Physics Learning Game is made used App Inventor 2 (AI2). Keywords: Serious Games, android, educational Games, App Inventor 2, Physics